Species delimitation in the Aloysia gratissima complex (Verbenaceae) following the phylogenetic species concept. (23rd December 2015) - Moroni, Pablo; O'Leary, Nataly; Filloy, Julieta
Abstract : The Aloysia gratissima complex is a group of 22 accepted, specific and infraspecific taxa, the boundaries of which are controversial. Various different authors have chosen different characters as criteria for delimiting taxa in this complex, which has been reflected in the variable number of accepted species. To resolve the taxonomy of this group, a modified population aggregation analysis, based on the phylogenetic species concept, was employed. As a result, the Aloysia gratissima complex is here circumscribed as compromising only four species, A. decipiens, A. gratissima s.s ., A. oblanceolata and A. schulziana . These species are sustained by a different combination of four characters, of the 16 qualitative attributes analysed. A new approach based on cluster analysis is proposed here delimiting varieties. As a consequence two varieties, supported by significant differences in quantitative characters, are recognized here: A. gratissima var . gratissima and A. gratissima var . sellowii . A complete taxonomic revision of the accepted taxa is presented and six new synonyms are proposed. A key, illustrations and geographical distribution maps are included. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2016, 180, 193–212.